Study of the qualitative and sensory properties of yogurt manufactured by adding medicinal and aromatic plant extract(mint) - Khalil, Isra'a Qassim Mohsen; Hussain , Mahdi Hassan (Journal of Kerbala for Agricultural Sciences, 2024)
This research aimed to study yogurt, to which an aqueous extract of the medicinal and aromatic plant (mint) was added to manufacture a new dairy product to improve and treat many different digestive system problems. They were using the lactic acid bacteria (Streptococcus thermophilus and Lactobacillus bulgaricus). The yogurt product was manufactured by adding an aqueous extract of mint with three concentrations of (1%), (2.5%), and (4%) (v/v) mint, and they were represented by N1, N2, and N3 treatments, respectively, as well as the control (C) treatment in which the yogurt was prepared without any addition. The treatments were stored for 21 days at (5±1)°C. The physicochemical and rheological properties were studied, which included measurement (pH, total acidity, viscosity, syneresis, and hardness), microbiological tests, as well as sensory evaluation on the first day of manufacture and after 7, 14, and 21 days of cold storage. The results showed no significant differences in the values of pH and total acidity, While significant differences were found in the values of syneresis, viscosity, and hardness. It was also observed that the numbers of starter bacteria varied for all treatments immediately after manufacturing, but during storage, a gradual decrease in their numbers was observed for all treatments, and the N3 treatment recorded the highest numbers of starter bacteria compared to the other treatments. Also, the results showed superiority of N2 and N3 treatments in the sensory evaluation of flavor, taste, texture and general acceptance.